La poesía de Domingo López Torres: hacia el surrealismo en Canarias. - Gutiérrez, José Ismael (2012)
Because of his political afiliation to the Socialist Party, the Canarian poet Domingo López Torres (1910-1937) was murdered in the beginnings of the Civil War after spending some months imprisonned. His compromise was not only political but also literary. Being an enemy of every type of tradicionalism, he sympathized with those renovative aesthetical tendencies that wanted to introduce the most progressist styles, ideas and conducts of 1930s Europe, which made him crucial in the process of reception of Surrealism in the island of Tenerife. This article describes López Torres’ gradual approach to the avant-garde movement led by André Breton. His two main works are analized with this aim:  Diario de un sol de verano and Lo imprevisto, both inedit until 1987 and 1981 respectively. While the first volume, written around 1928, connects with the principles of Ultraism, with the Regionalism proposed by his fellow countryman Pedro García Cabrera, with Juan Ramón Jimenez’s “Pure Poetry” or with Lorca’s and Alberti’s neopopulist facets, the second one, composed in the prison of Fyffes, just before he died, reveals the use of openly surrealistic procedures and images